Creative calendar collection. - Bigbros workshop (Barcelona : Linksbooks, 2011)
A calendar is a tool that helps us not to lose sight of our commitments and daily activities and knowing how important calendars play a part in our lives - Creative Calendar Collection comprises many interesting specially selected calendars of varied design from across the globe. These designs push the limits of calendars both aesthetically and conceptually. With calendars contributed by various designers and studios like Thought (JP), Typodarium, Kenji Yano and many more - Creative Calendar Collection is a good keep.
boek